Process Approach to Cost of Quality - Katarzyna Szczepańska (Contemporary Economics)
Contemporary understanding comprehending cost of quality is connected both with the sphere of the management, as well as the operational activity. Borders of considering the category of quality costs moved beyond the technical – technological area. Trial including costs let the quality for classifying them with reference to all action carried out in the modern enterprise. Standard models of quality costs and the activity – based costing appointed new prospects of economics of the quality in the business administration.